Experimental and numerical study of the behaviour of piles subjected to lateral soil movement - Pan, Jieliang (2008)
Experimental and numerical studies were carried out on the behaviour of piles in soft clay when subjected to lateral forces induced by horizontal soil movements from nearby construction activities such as deep excavations, tunnelling and approach embankments. The main objective of this study was to gain a better understanding of the interaction between the moving soil and the pile around it and to investigate the limiting soil pressures (maximum soil pressures) acting on single piles and pile groups as well as the relevant parameters influencing the behaviour of piles subjected to lateral soil movements.